Peran Asah (3A) Pengasuh dengan Perkembangan Bahasa Anak Usia Toddler di Taman Penitipan Anak - Ilya Krisnana; Praba Diyan Rachmawati; Mar’atus Sholihah (Jurnal Ners, 2016)
Introduction: Role of caregiver in the day care is really important in every aspect of children development, especially language development. This study aimed to analyze the relationship between role of caregiver in giving stimulation and language development toddler in 3 day care in Surabaya. Methods: This study was using cross-sectional study. The population were children and caregivers in day care with purposive sampling. 16 caregivers and 33 children as respondents, taken according to inclusion and exclusion criteria. The dependent variable was role of cargiver in giving stimulation. The independent variable was the toddler language development. Data collection for caregivers stimulation through observation sheets and for language development children through Denver II, and were analyzed by using non-parametric correlation analysis (Spearman rho) with significance value α=0.05. Result: The result showed that caregiver in giving stimulation has correlate with language development toddler (p-value = 0.002, r = 0.0510). Discussion: It can be concluded that correlation between role of cargiver in giving stimulation with language development toddler was significant and has strong enough correlation. Further research need to identify more factors such as genetic factor and the other aspects of environmental factor.